CHLORELLA VULGARIS FOR BIOSORPTION OF HEAVY METALS AND POME TREATMENT - AHMAD, ASHFAQ (2018)
This study focuses on the utilization of freely suspended and Ca-alginate immobilized algal cells in a reactor system for heavy metals biosorption and POME treatment.